2010
DOI: 10.1002/cncr.25094
|View full text |Cite
|
Sign up to set email alerts
|

Serum sE‐selectin levels and carcinoembryonic antigen mRNA‐expressing cells in peripheral blood as prognostic factors in colorectal cancer patients

Abstract: BACKGROUND: This study analyzed the possible prognostic value of presurgical serum soluble (s)E-selectin levels and/or carcinoembryonic antigen (CEA) mRNA positivity in predicting the disease-free survival of colorectal cancer (CRC) patients. METHODS: CEA mRNA (obtained from blood-borne cells by reverse transcriptase-polymerase chain reaction [RT-PCR]), tumor necrosis factor-a (TNF-a), and sE-selectin levels were analyzed in blood samples obtained from 78 patients with primary (n ¼ 62) or recurrent (n ¼ 16) CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Thus, increased expression levels of sE-selectin were associated with reduced overall survival in breast cancer (49). Similarly, pre-surgical sE-selectin expression levels were higher in patients with colorectal cancer (43 ng/ml) compared with patients with benign diseases (43 ng vs. 31 ng/ml) and were positively associated with carcinoembryonic antigen tumor marker and poorer prognosis (both P<0.001) (50). However, a study of microarray data from 1,809 breast cancer patients with no previous treatment history revealed that E-selectin expression level was associated with longer survival times (HR, 0.67; CI 95%, 0.54–0.83; P=0.001) (51).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased expression levels of sE-selectin were associated with reduced overall survival in breast cancer (49). Similarly, pre-surgical sE-selectin expression levels were higher in patients with colorectal cancer (43 ng/ml) compared with patients with benign diseases (43 ng vs. 31 ng/ml) and were positively associated with carcinoembryonic antigen tumor marker and poorer prognosis (both P<0.001) (50). However, a study of microarray data from 1,809 breast cancer patients with no previous treatment history revealed that E-selectin expression level was associated with longer survival times (HR, 0.67; CI 95%, 0.54–0.83; P=0.001) (51).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that sE-selectin is highly expressed in colorectal cancer and is closely associated with the progression, recurrence and metastasis of cancer (31,32). It was observed that the serum levels of sE-selectin were significantly increased in CSCC patients and were correlated with FIGO stage and tumor size.…”
Section: ------------------------------------------------------------mentioning
confidence: 94%
“…Cheng et al (42) reported that GRO-1 may be a promising adverse prognostic molecular marker, and Miyake et al (43) confirmed the poor prognostic value of GRO-1 in bladder cancer. Numerous studies have demonstrated the prognostic value of sE-selectin in colorectal cancer (31,34). Our findings suggested that GRO-1 and sE-selectin may have an impact on the prognosis of CSCC patients by affecting FIGO stage or lymph node metastasis, thus GRO-1 and sE-selectin were not independent prognostic risk factors.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…[18][19][20][21] High presurgical serum levels of sE-selectin correlate with increased recurrence and poor survival in colon cancer. 22,23 It can be an independent prognostic factor for patients with advanced lung cancer. 24 Although it is difficult to draw solid conclusions due to the fact that we compared the changes in cytokine levels across different dose levels, our findings suggest that serum sE-selectin may be explored as a potential biomarker for monitoring response to chemotherapy.…”
Section: All Grades Grades 3/4 All Grades Grades 3/4 All Grades Gradementioning
confidence: 99%